Calculation of the stability of the equilibrium form of discrete systems - Shkurupiy, Oleksandr; Mytrofanov, Pavlo; Dovzhenko, Oksana; Pohribnyi, Volodymyr (International Journal of Engineering and Technology, 2018)
On the basis of the displacement method, together with the methods of iterations and half-division, an algorithm for stability calculation of the first kind equilibrium form of compressed reinforced concrete columns with hinged fixing at the ends, considering the stiffness changing was developed. The use of the above methods makes it possible to determine the minimum critical load or stress at the first bifurcation and their stability loss corresponding form. The use of matrix forms contributes to simplification of high order stability loss equation. This approach allows to obtain the form of stability loss that corresponds to the critical load.Â Â
Keywords: equilibrium form; compressed reinforced concrete columns; software complex; stability loss equation.